IMMORALITY: SEBUAH STUDI BIBLIKAL-SISTEMATIS - Iman Kristina Halawa (Sekolah Tinggi Teologi Arastamar Bengkulu, 2019)
At present there are many moral deviations in human life. Moral deviations have permeated the human life, namely: in the fields of politics, economics, education, art, philosophy and the church. These deviations occur because of a lack of complete understanding of immorality. Therefore through this paper we will present phenomenologically moral deviations in several aspects of human life, then in this paper will discuss the roots of the phenomenon of moral deviance in a biblical-systematic manner. Because the author believes that the fact of immorality was present at the time of the Bible (PL & amp; NT) and the Bible also provides facts about how God responds to the events of immorality that occur. So that through this writing believers can determine attitudes toward current immorality events according to how God stands in the Bible.